Conceptual structure of English and Ukrainian riddles: a comparative analysis - Pavkin, D. M. (Cognition, Communication, Discourse, 2018)
The paper offers a cognitive approach to the analysis of riddles. The necessity of such approach is determined by riddles being important constituents of the linguistic image of the world which is a reflection of the ethnic conceptual image of the world. The author exposes five characteristic features of the riddle conditioning its treatment as a peculiar type of the phraseological unit. Conceptual analysis of English and Ukrainian riddles has two objectives in view: to model the conceptual arrangement of objects the riddles refer to, and to expose the features these objects display in the riddles. The author argues that the revealed differences pertain to idioethnic specificity of the two communities